Challenges in Urology during the COVID-19 Pandemic - Jin, Peng (Urol Int, 2020)
The COVID-19 pandemic has caused a global health threat. This disease has brought about huge changes in the priorities of medical and surgical procedures. This short review article summarizes several test methods for COVID-19 that are currently being used or under development. This paper also introduces the corresponding changes in the diagnosis and treatment of urological diseases during the COVID-19 pandemic. We further discuss the potential impacts of the pandemic on urology, including the outpatient setting, clinical work, teaching, and research.